Self-Esteem dan Makna Hidup pada Pensiunan Pegawai Negeri Sipil (PNS) - Riris Setyarini; Nuryati Atamimi (Jurnal Psikologi, 2011)
The main purpose of this research is to investigate the correlation between self-esteem and life meaning in retired civil servants of Republic of Indonesia. The additional aim is to determine thelevel of self-esteem and life meaning amongst the subjects. There were 32 retired civil servants selected as research subjects using the purposive sampling technique. This research was conducted onOctober 13, 2012, from 09:00 to 11:30 a.m. at the PWRI Srandakan office in Srandakan, Bantul, Yogyakarta. The researcher distributed questionnaire forms, consisted of 29 statements for self-esteem scale and 34 statements for life meaning scale. Researcher interviewed five subjects to obtain additional information and enrich the discussion. The results showed that there is a positive andsignificant correlation between self-esteem and life meaning in the retired civil servants, r=0.615, p= 0.000 (α<0.01). The research subjects scored higher than expected in the mentioned scales because the empiric score is larger than hypothetic score. The effective contribution of self-esteem variable towards life meaning is 38%.